2022
DOI: 10.1021/acsestwater.2c00299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heterogeneous Metals on the Generation of Persistent Free Radicals as Critical Redox Sites in Iron-Containing Biochar for Persulfate Activation

Abstract: Metal components have critical influences on the generation of persistent free radicals (PFRs) in biochar. However, little is known about the effect on the formation of PFRs brought about by interactions among metal components when pyrolyzing biomass containing multiple metal components (e.g., sewage sludges and hyperaccumulators) for biochar. Herein, iron-modified biochar (FeO/BC) and iron-containing bimetallic oxide-loaded biochar (ZnFeO/BC, CoFeO/BC, and NiFeO/BC) were prepared. Due to the synergistic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Usually, free radicals are highly unstable and rapidly react with each other, thus being destroyed as soon as they form, with a consequent very short half-life. However, it has been found that in BC, some free radicals, named persistent free radicals (PFRs), like the radicals that naturally occur in the environment, known as environmental persistent free radicals (EPFRs), can remain stable for months and play a crucial role in the subsequent reactions of oxidative degradation carried out by BC containing them [25,107,125,126] (Figure 6). Unlike other free radicals, PFRs are resonance-stabilized since they are bound to the external or internal surface of solid particles of BC.…”
Section: Persistent Free Radicals (Pfrs)mentioning
confidence: 99%
“…Usually, free radicals are highly unstable and rapidly react with each other, thus being destroyed as soon as they form, with a consequent very short half-life. However, it has been found that in BC, some free radicals, named persistent free radicals (PFRs), like the radicals that naturally occur in the environment, known as environmental persistent free radicals (EPFRs), can remain stable for months and play a crucial role in the subsequent reactions of oxidative degradation carried out by BC containing them [25,107,125,126] (Figure 6). Unlike other free radicals, PFRs are resonance-stabilized since they are bound to the external or internal surface of solid particles of BC.…”
Section: Persistent Free Radicals (Pfrs)mentioning
confidence: 99%
“…If BC is conserved under vacuum, lifetime of PFRs could be infinite (no decay radicals), while when air-exposed they react with molecular oxygen in the air, decay over time, thus producing ROS. Similarly, in aqueous systems, PFRs act as transition metals like Fe 2+ , forming ROS, as well [301][302][303][304]. PFRs are categorized into three classes, i.e., oxygen-centered PFRs (OCPFRs), carbon-centered PFRs (CCPFRs), and oxygenated carbon-centered radicals (CCPFRs-O).…”
Section: Biochar-derived Persistent Free Radicals (Pfrs)mentioning
confidence: 99%